2020
DOI: 10.1097/icl.0000000000000730
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bandage Contact Lens Exchange on Pain and Healing After Photorefractive Keratectomy—A Randomized Control Trial

Abstract: Objective: To evaluate the corneal re-epithelialization and patient-perceived pain after bandage contact lens (BCL) exchange on day one, after photorefractive keratectomy (PRK). Methods: A randomized controlled trial, of all patients who underwent bilateral transepithelial-PRK (trans-PRK) or bilateral alcohol debridement and PRK (A-PRK), between March and October 2019. One eye of each patient was randomly assigned to BCL exchange on the first postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Recently, AlDahash et al achieved that BCL exchange during the first PRK postoperative day vaguely reduce pain score and not vary epithelial recovery. 7 In conclusion, Samfilcon A, with the higher oxygen permeability and water content, reported the lowest pain score and reepithelization zone on postoperative day 1. The differences between the materials were no longer statistically significant on the third day after the PRK surgery.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Recently, AlDahash et al achieved that BCL exchange during the first PRK postoperative day vaguely reduce pain score and not vary epithelial recovery. 7 In conclusion, Samfilcon A, with the higher oxygen permeability and water content, reported the lowest pain score and reepithelization zone on postoperative day 1. The differences between the materials were no longer statistically significant on the third day after the PRK surgery.…”
mentioning
confidence: 80%
“…Recently, AlDahash et al achieved that BCL exchange during the first PRK postoperative day vaguely reduce pain score and not vary epithelial recovery. 7…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Exchanging BCL every day after PRK lowered postoperative pain on day 1 (P¼0.009) compared with the eye treated with the same BCL without exchange, whereas the response was similar thereafter. 44 The removal of BCL on the fourth or seventh postoperative day did not affect the pain response on day 1 (P¼0.20). The removal of BCL on the seventh postoperative day had lower pain scores compared with the removal on the fourth postoperative day (P¼0.07).…”
Section: Photorefractive Keratectomymentioning
confidence: 95%
“…The studies reported uniform administration of postoperative medication regimens such as antibiotics, steroids (betamethasone, loteprednol, prednisolone, and fluorometholone), NSAIDs (diclofenac, nepafenac, and ketorolac), and opioids (in few studies) were applied to both eyes including control or between comparisons of BCLs eyes after PRK. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] Among other outcomes, epiphora scores and comfort scores improved by day 3 after surgery on BCL application, whereas photophobia scores and foreign body sensation decreased by the third day after surgery. 35,37,42,54,55 Pain is known to subside when re-epithelialization of the cornea is completed.…”
Section: Photorefractive Keratectomymentioning
confidence: 99%